Comparison on losses and flux distribution among the three of 3 phase distribution transformer 1000kVA assembled from various amount of layer of transformer core lamination - Ismail, Daut; Dina Maizana, Maiz Ahmad; Shuhaimi, Zakaria; S. Uthman; Soib, Taib (Universiti Kuala Lumpur (UniKL), 2008)
Organized by Universiti Kuala Lumpur (UniKL), 11th - 13th 2007 at Kuala Lumpur, Malaysia.